Identificação de raças bovinas brasileiras por meio de análise tricológica - Felix, Gisele Aparecida (2016)
Trichology is a method to analyze micro-structural patterns of scarf-skin scales arrangements and medullary cells found in mammals guard hair. The present study was conducted to identify Caracu, Curraleiro Pé-Duro, Pantaneiro and Nellore bovine breeds by trichological morphology and morphometry, as well as validate the technique compared with genetic characterization. This study was presented in chapters. First, a review on trichology application on mammal species and breeds identification with basic concepts necessary for understanding trichology analysis and its applications. The second chapter was composed by characterization of guard hair of Caracu, Curraleiro Pé-Duro and Pantaneiro (Bos taurus taurus) and of Nellore (Bos taurus indicus), Brazilian bovine breeds, through trichology analysis, to assess the possibility of using this technique as a racial marker. Morphological and morphometric descriptions were held by 160 cattle (40 animals/breeds). Sub-samples of each bovine were made until quality slides were obtained. Morphology was determined through dichotomous keys and measures were carried out in the cuticle scale and in the hair shield matrix. Results indicated that trichology and genetic evaluation were similar in the point of view of classification of individuals within racial groups. Therefore, the technique can be considered useful as a marker for bovine breeds.